Reformasi Konstitusi Dalam Transisi Menuju Demokrasi - Cornelis Lay; Amalinda Savirani (Faculty of Social and Political Sciences, Universitas Gadjah Mada, 2000)
Constitutional reform is one of the most important ways undertaken by some transitional regime to establish a democratic government. This kind of reform has many models. In Spain i t is called reforma pactada-ruptura pactada involving